Animal Toxicology Studies on the Male Reproductive Effects of 2,3,7,8-Tetrachlorodibenzo-p-Dioxin: Data Analysis and Health Effects Evaluation - Zhang, Tongtong; Zhou, Xiang; Ren, Xiaohan; Zhang, Xu; Wu, Jiajin; Wang, Shangqian; Wang, Zengjun (Frontiers in Endocrinology, 2021)
2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is a well-known environmental poison that exist in the environment for many years. However, its effect on the male reproductive system has not been clearly stated. We conducted a meta-analysis of the effect of TCDD on the male reproductive system of rodents about TCDD. Results showed that that TCDD exposure reduced the testis weight (weighted mean difference [WMD]: −0.035, 95% confidence interval [CI]: −0.046 to −0.025), sperm count (WMD: −35, 95% CI: −42.980 to −27.019), and blood testosterone concentration (WMD: −0.171, 95% CI: −0.269 to −0.073). According to our research results, TCDD can cause damage to the male reproductive system of rodents through direct or indirect exposure. In order to further explore the potential hazards of TCDD to humans, more human-related research needs to be carried out.